Open versus Endovascular Repair of Abdominal Aortic Aneurysm in the Elective and Emergent Setting in a Pooled Population of 37, 781 Patients: A Systematic Review and Meta-Analysis. (2nd April 2014) - Thomas, Dustin M.; Hulten, Edward A.; Ellis, Shane T.; Anderson, David M. F.; Anderson, Nathan; McRae, Fiora; Malik, Jamil A.; Villines, Todd C.; Slim, Ahmad M.
Abstract : Background . We evaluated the incidence of mortality and myocardial infarction (MI) in endovascular repair (EVAR) as compared to open aneurysm repair (OAR) in both elective and ruptured abdominal aortic aneurysm (AAA ) setting. Methods . We analyzed the rates of 30-day mortality, 30-day MI, and hospital length of stay (LOS) based on comparative observation and randomized control trials involving EVAR and OAR. Results . 41 trials compared EVAR to OAR with a total pooled population of 37, 781 patients. Analysis of elective and ruptured AAA repair favored EVAR with respect to 30-day mortality with a pooled odds ratio of 0.19 (95% CI 0.17–0.20; I 2 = 88.9 % ; P < 0.001 ). There were a total of 1, 835 30-day MI events reported in the EVAR group as compared to 2, 483 events in the OAR group. The pooled odds ratio for elective AAA was 0.74 (95% CI 0.58–0.96; P = 0.02 ) in favor of EVAR. The average LOS was reduced by 296.75 hrs (95% CI 156.68–436.82 hrs; P < 0.001 ) in the EVAR population. Conclusions . EVAR has lower rates of 30-day mortality, 30-day MI, and LOS in both elective and ruptured AAA repair.